ANALISIS PENGARUH INDEKS PERSEPSI KORUPSI DAN INDIKATOR MAKROEKONOMI TERHADAP INVESTASI ASING LANGSUNG DI NEGARA-NEGARA ASEAN TAHUN 2013-2022 - Ardina, Mayang; Astuti, Rini Dwi (Jurnal Ekonomi-Qu, 2025)
This study aims to analyze the effect of corruption perception index, market size, inflation, and trade openness on foreign direct investment in eight ASEAN countries in 2013-2022. The data used in this study are secondary data, namely data on foreign direct investment, corruption perception index, market size, inflation, and trade openness in eight ASEAN countries in 2013-2022. The analytical tool used in this research is panel data regression with Random Effect Model. The results of this study indicate that the corruption perception index variable has a negative and significant effect on foreign direct investment in eight ASEAN countries in 2013-2022, while the market size, inflation, and trade openness variables have a positive and significant effect on foreign direct investment in eight ASEAN countries in 2013-2022.